Strategy for the development of research competence in university students: Irapuato Institute University case study - Guerra Olivares, Miguel Ángel (2024)
The research focuses on designing a strategy for the development of research competence in university students of the Industrial Engineering degree at the UII. The quantitative approach methodology is experimental with an intact natural group and a group with intervention, where the intervention will be to put into practice the Workshop "How to do Research in Engineering" to later apply an evaluative rubric, analyzing the data in Minitab Statistical Software using procedures hypothesis testing and confidence intervals to compare the means of the interventions. The results of the experiment with a p-value of 0.013 show a significant change in the dependent variable: research competence, achieving the design of the strategy for the development of research competence in students of the Industrial Engineering degree at the UII.